MULTIPLE-CRITERIA DECISION ANALYSIS MENGGUNAKAN COMPOSITE PERFORMANCE INDEX PADA SISTEM PEMILIHAN IP CAMERA - Murien Nugraheni; Fryda Fatmayati; Rini Nuraini; Mokhammad Hadi Prayitno (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
IP Camera is a camera used for monitoring and security with the ability to transmit images over a network connected to the internet protocol. To choose an IP camera, users must know product performance and specifications, so it takes time in the selection process. The purpose of this study is to apply the Multiple-Criteria Decision Analysis (MCDA) approach with the Composite Performance Index (CPI) method in determining the best IP camera. The CPI approach can obtain the best option by assessing the combined index and then sorting it from the highest to the lowest value. From the case studies that have been carried out, the best alternative is obtained, namely Dahuan IMOU Bullet 2C (A4) with a value of 145, then Xiaomi Security Camera 2K (A3) with a value of 140, Bardi Smart Outdoor Static IP Camera (A2) with a value of 130 and EZVIZ C6N (A1) with a value of 105. These results are the same as the output obtained on the built DSS, this means that the system calculation results can be said to be valid. Based on the evaluation results through black-box testing, it shows that all the functions of the existing features can work properly.